Development of an in vitro procedure to determine ruminal availability of protein - C.K. Schoenholz; James S. Drouillard; C.K. Armendariz; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
A series of in vitro experiments was conducted to determine the ruminal availability of protein from grains. Procedures were based on assumptions that 1) ruminal availability of protein is first-limiting to microbial growth, 2) accumulation of microbial cells accurately predicts ruminal protein availability,3) cytosine can be used to accurately estimate microbial cell mass, and 4) cytosine is present in microorganisms but not in feeds. Cytosine content of in vitro cultures was measured by high performance liquid chromatography. Early experiments determined that adding 0.75 g soluble starch provided enough energy that culture growth depended on available protein. In the final experiment, microbial cytosine was measured for several processed grains and for graded levels of sodium caseinate (as a standard for comparison). Cytosine increased as sodium caseinate levels increased. Heat-processed grains yielded less cytosine than grains processed without heat. Cytosine accumulation during in vitro fermentation provides a useful measure of ruminal protein availability.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Cytosine; Protein degradability; Microbial growth